ANALISIS GETARAN DAN KEBISINGAN PADA MESIN KAPAL PENUMPANG - Bobo, Eugenius (Blueprint Journal, 2025)
This study aims to analyze vibration and noise in passenger ship engines and their impact on the safety and comfort of crew and passengers. The research method used is measuring vibration and noise in passenger ship engines using vibration measuring instruments and sound level meters. This study revealed that vibration and noise levels in passenger ship engines often exceed the limits set by IMO, indicating the need for control measures. This study also shows that high levels of vibration and noise can contribute to fatigue and health problems for crew and passengers. To overcome this, it is recommended to install a vibration isolation system and sound-absorbing materials to reduce vibration and noise levels in passenger ship engines.